2024
DOI: 10.1037/xge0001476
|View full text |Cite
|
Sign up to set email alerts
|

Demands on perceptual and mnemonic fidelity are a key determinant of age-related cognitive decline throughout the lifespan.

Helena M. Gellersen,
Jessica McMaster,
Ayat Abdurahman
et al.

Abstract: Aging results in less detailed memories, reflecting reduced fidelity of remembered compared to real-world representations. We tested whether poorer representational fidelity across perception, short-term memory (STM), and long-term memory (LTM) are among the earliest signs of cognitive aging. Our paradigm probed target–lure object mnemonic discrimination and precision of object-location binding. Across the lifespan, cognitive deficits were observed in midlife when detailed stimulus representations were require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 173 publications
(308 reference statements)
0
2
0
Order By: Relevance
“…Establishing to what extent memory impairments are a pervasive effect of age or whether they vary depending on environmental factors or learned strategies based on cultural context is an important question. Impairments in memory, particularly in terms of the level of detail or specificity, can be pronounced with age and in age-related disorders such as amnestic mild cognitive impairment (aMCI) or Alzheimer’s disease (AD) (Balota et al, 1999, Bowman et al, 2019; Paige, Cassidy, Schacter, & Gutchess, 2016; Gellersen, McMaster, Abdurahman, & Simons, 2024), so exploring the extent to which environmental factors can modulate the effects of aging on memory could inform the development of effective interventions to mitigate age-related deficits in memory.…”
Section: Effects Of Age On Cross-cultural Differences In the Neural C...mentioning
confidence: 99%
“…Establishing to what extent memory impairments are a pervasive effect of age or whether they vary depending on environmental factors or learned strategies based on cultural context is an important question. Impairments in memory, particularly in terms of the level of detail or specificity, can be pronounced with age and in age-related disorders such as amnestic mild cognitive impairment (aMCI) or Alzheimer’s disease (AD) (Balota et al, 1999, Bowman et al, 2019; Paige, Cassidy, Schacter, & Gutchess, 2016; Gellersen, McMaster, Abdurahman, & Simons, 2024), so exploring the extent to which environmental factors can modulate the effects of aging on memory could inform the development of effective interventions to mitigate age-related deficits in memory.…”
Section: Effects Of Age On Cross-cultural Differences In the Neural C...mentioning
confidence: 99%
“…In other studies, it was reported that the likelihood of retrieval success declines faster than precision as a function of retention interval (Berens et al, 2020). By contrast, precision is more sensitive than success to healthy aging (Gellersen et al, 2024; Korkki et al 2020; Nilakantan et al, 2018) and damage to the hippocampus (Nilakantan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%